2021
DOI: 10.14744/tjtes.2021.06777
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 Pandemic on pediatric appendicitis hospital admission time and length of hospital stay

Abstract: BACKGROUND: Appendicitis is one of the most common surgical emergencies among children. In this retrospective clinical study, we attempted to determine the effects of the COVID-19 pandemic period on hospital admission time and length of hospital stay (LOS) in pediatric appendicitis cases. METHODS:We retrospectively compared pediatric appendectomies from the date of the first reported COVID-19 case to June 1, 2020, which is considered as the start of the normalization process, with pre-pandemic pediatric append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Taşçi et al . 19 found that the interval between the onset of symptoms and hospital admission in pediatric patients with appendicitis increased by 2 days during the COVID-19 pandemic, which is consistent with another retrospective study that revealed a significantly longer time between symptom onset and presentation to the emergency department during the peak of the pandemic, with a few patients waited up to 14 days before seeking medical attention 17 .…”
Section: Prevalence and Epidemiology Of Acute Appendicitis In Vulnera...supporting
confidence: 85%
“…Taşçi et al . 19 found that the interval between the onset of symptoms and hospital admission in pediatric patients with appendicitis increased by 2 days during the COVID-19 pandemic, which is consistent with another retrospective study that revealed a significantly longer time between symptom onset and presentation to the emergency department during the peak of the pandemic, with a few patients waited up to 14 days before seeking medical attention 17 .…”
Section: Prevalence and Epidemiology Of Acute Appendicitis In Vulnera...supporting
confidence: 85%
“…The authors concluded that delayed hospital admission did not alter outcomes. Another interesting observation was that parental education did not contribute to increased time before hospital admission [28]. Sheath et al found a similar 2-day delay to presentation with more complicated appendicitis cases [16].…”
Section: Time To Hospital Admission Duration Of Symptoms and In-hospi...mentioning
confidence: 95%
“…Pediatric appendicitis outcomes can also be affected by lower socio-economic status as a consequence of hindered access to healthcare. This was studied before the pandemic [28,[57][58][59][60]. The associations between pediatric appendicitis outcomes and lower socio-economic status groups and poor nations that were highly affected by the pandemic warrant further study as there is no relevant evidence to date.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation